Identification of Algerian Field-Caught Phlebotomine Sand Fly Vectors by MALDI-TOF MS. - Ismail Lafri; Lionel Almeras; Idir Bitam; Aurelia Caputo; Amina Yssouf; Claire-Lise Forestier; Arezki Izri; Didier Raoult; Philippe Parola (Public Library of Science (PLoS), 2016)
BACKGROUND:Phlebotomine sand flies are known to transmit Leishmania parasites, bacteria and viruses that affect humans and animals in many countries worldwide. Precise sand fly identification is essential to prevent phlebotomine-borne diseases. Over the past two decades, progress in matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) has emerged as an accurate tool for arthropod identification. The objective of the present study was to investigate the usefulness of MALDI-TOF MS as a tool for identifying field-caught phlebotomine. METHODOLOGY/PRINCIPAL FINDINGS:Sand flies were captured in four sites in north Algeria. A subset was morphologically and genetically identified. Six species were found in these areas and a total of 28 stored frozen specimens were used for the creation of the reference spectrum database. The relevance of this original method for sand fly identification was validated by two successive blind tests including the morphological identification of 80 new specimens which were stored at -80°C, and 292 unknown specimens, including engorged specimens, which were preserved under different conditions. Intra-species reproducibility and inter-species specificity of the protein profiles were obtained, allowing us to distinguish specimens at the gender level. Querying of the sand fly database using the MS spectra from the blind test groups revealed concordant results between morphological and MALDI-TOF MS identification. However, MS identification results were less efficient for specimens which were engorged or stored in alcohol. Identification of 362 phlebotomine sand flies, captured at four Algerian sites, by MALDI-TOF MS, revealed that the subgenus Larroussius was predominant at all the study sites, except for in M'sila where P. (Phlebotomus) papatasi was the only sand fly species detected. CONCLUSION:The present study highlights the application of MALDI-TOF MS for monitoring sand fly fauna captured in the field. The low cost, reliability and rapidity of MALDI-TOF MS analyses opens up new ways in the management of phlebotomine sand fly-borne diseases.